2012
DOI: 10.1007/s10616-011-9417-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the green florescence protein labeling method for tracking implanted mesenchymal stem cells

Abstract: Although green fluorescent protein (GFP) labeling is widely accepted as a tracking method, much remains uncertain regarding the retention of injected GFP-labeled cells implanted in ischemic organs. In this study, we evaluate the effectiveness of GFP for identifying and tracking implanted bone marrow-mesenchymal stem cells (BM-MSCs) and the effect of GFP on the paracrine actions of these cells. MSCs isolated from rat femur marrow were transduced with a recombinant adenovirus carrying GFP. After transplantation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 31 publications
(35 reference statements)
0
20
0
1
Order By: Relevance
“…To understand this process in detail and to ensure safety and efficacy, it is crucial to detect the fate and distribution of MSCs delivered to wound sites. GFP has already become the most suitable biomarker for tracking MSCs due to its biocompatibility, safety, nontoxicity and high detectability [36, 37]. GFP-tagged MSCs derived from transfection methods have been commonly used as donor cell sources in previous studies [36, 38, 39].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To understand this process in detail and to ensure safety and efficacy, it is crucial to detect the fate and distribution of MSCs delivered to wound sites. GFP has already become the most suitable biomarker for tracking MSCs due to its biocompatibility, safety, nontoxicity and high detectability [36, 37]. GFP-tagged MSCs derived from transfection methods have been commonly used as donor cell sources in previous studies [36, 38, 39].…”
Section: Discussionmentioning
confidence: 99%
“…GFP has already become the most suitable biomarker for tracking MSCs due to its biocompatibility, safety, nontoxicity and high detectability [36, 37]. GFP-tagged MSCs derived from transfection methods have been commonly used as donor cell sources in previous studies [36, 38, 39]. Previous results demonstrated that GFP-tagged MSCs could be traced for 4 weeks after surgical treatment [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MSCs were also characterized by differentiation toward adipogenic and osteogenic lineages using previously described protocols. 13 The purified MSCs at passage (P)3 were transduced with a lentiviral vector carrying a GFP reporter gene as described previously. 14,15 Immune antigen expression in MSCs The immunophenotype (MHC I, MHC II, CD40, CD80, CD86) of MSCs was examined by flow cytometry on a FACSCanto II (BD Pharmingen, San Diego, CA, USA) with specific phycoerythrin-conjugated monoclonal antibodies (eBioscience, San Diego, CA, USA) and performed as previously described.…”
Section: Animalsmentioning
confidence: 99%
“…Studies of the effects of stem cell implantation in partially transected infraspinatus tendons in sheep [80] have demonstrated that MSCs had a beneficial effect on induced tendon pathology. Such effects were observed not only when injected acutely, but also in the face of established degenerative change, although there was no effect of MSCs on the actual lesion site.…”
Section: Review Smith Garvican and Fortiermentioning
confidence: 99%